The Impact of Celebrity Endorsement on Young Female Consumers’ Purchase Intention: The Mediating Effects of Customer Attitude (A study in Indonesia Beauty Industry) - Permatasari, Intan Ayu; Widodo, Arry; Rubiyanti, Nurafni; Silvianita, Anita (Formosa Journal of Multidisciplinary Research, 2025)
This research explores the relationship between celebrity endorsement and purchase intention among young female consumers in Indonesia's beauty industry, emphasizing the mediating role of customer attitudes. In this digital era, the findings reveal that celebrity endorsements positively impact purchase intentions. Specifically, the visibility, credibility, and attractiveness of celebrities, leading to increased purchase intentions. Moreover, customer attitudes serve as a crucial mediator between celebrity endorsement and purchase intention. The study employs a quantitative approach, utilizing a structured questionnaire distributed to sample of young female consumers respondents. This study contributes to the understanding of marketing strategies in the beauty industry, suggesting that brands should carefully select celebrity endorsers who resonate with their target audience to maximize effectiveness.